2014
DOI: 10.1038/ncomms6264
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial defects trigger proliferation of neighbouring cells via a senescence-associated secretory phenotype in Drosophila

Abstract: Cell-cell interactions play important roles in epithelial tumorigenesis. Here we show in Drosophila imaginal epithelium that Ras activation and mitochondrial dysfunction, frequent alterations in cancers, cause cellular senescence and senescence-associated secretory phenotype (SASP), which leads to overgrowth of neighbouring tissue. Ras-activated cells express several hallmarks of cellular senescence such as elevation of senescence-associated b-galactosidase activity, upregulation of the Cdk inhibitor Dacapo, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 57 publications
4
77
1
Order By: Relevance
“…9, 10, 11 In Ras-driven epithelial overgrowth, studies in Drosophila have revealed that impairment of cell polarity or mitochondrial functions enhance tumour growth and invasion via activation of the Jun kinase (JNK) stress response pathway, faithfully recapitulating some of the features responsible for tumour progression in human cancers. 11, 12, 13, 14, 15 …”
Section: Introductionmentioning
confidence: 99%
“…9, 10, 11 In Ras-driven epithelial overgrowth, studies in Drosophila have revealed that impairment of cell polarity or mitochondrial functions enhance tumour growth and invasion via activation of the Jun kinase (JNK) stress response pathway, faithfully recapitulating some of the features responsible for tumour progression in human cancers. 11, 12, 13, 14, 15 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Ras V12 / mito −/− cells cause cell‐cycle arrest through ROS production and undergo p53‐dependent cellular senescence (Fig. a) . Overexpression of p53 inside Ras V12 clones is sufficient to induce ONCs and non‐autonomous overgrowth.…”
Section: Non‐autonomous Tumor Progression By Oncsmentioning
confidence: 98%
“…Activated JNK coupled with oncogenic Ras could then inactivate the hippo pathway in senescent cells, stimulating secretion of Unpaired (an Interleukin-6 homologue) and Wingless (a Wnt homologue). Eventually, these secreted factors could cooperate with Ras signaling in neighboring cells (which have normal mitochondrial function), resulting in overgrowth of neighboring tissue 68,69 .…”
Section: Clonal Cooperation and Tumor Malignancymentioning
confidence: 99%